Old South Plantation Nostalgia - David Anderson (The Routledge Handbook of Nostalgia, 2024)
This chapter examines nostalgia for the plantation era South. Beginning in the 1830s, white southerners, in response to criticism of slavery, presented a nostalgic defence of the plantation system and the society built upon it. An idyllic portrayal of southern plantation life in the literature of the antebellum period imagined a South wedded to a chivalric code and traditions rooted in the past. Confederate defeat and Reconstruction, as well as the New South’s embrace of the Lost Cause, strengthened nostalgia for the Old South. By the 1880s and 1890s, nostalgia had become an influential force in shaping perceptions of the South’s history and its people. Many Gilded Age Americans, North and South, imagined the antebellum era – the plantation its binding symbol – as a perfect model of society, one blessed by racial harmony, stable class hierarchies, and defined gender roles that contrasted with the industrialisation and urbanisation of the late-19th century. During this time, as southern states enacted laws to disenfranchise black voters and segregate the races, African Americans and others set out to challenge the nostalgic image of the Old South and thus contest dominant white narratives of southern history.